2008
DOI: 10.1002/chem.200701686
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Assemblies of Tripodal Porphyrin Hosts and C60

Abstract: The self-assembly of two tripodal porphyrin hosts in the presence of C(60), in the solid state, has been studied using synchrotron X-ray crystallography, and in solution by using (1)H NMR and fluorescence spectroscopies. The binding affinities, stoichiometries and geometries strongly depend on the size of the porphyrin host. Intramolecular and/or intermolecular porphyrin-fullerene interactions are observed in the co-crystallites and in each case, the trimer exhibits a "tweezers-like" structural motif. The soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 70 publications
0
37
0
Order By: Relevance
“…We will conclude this section dedicated to porphyrin tweezers for fullerenes with the work on tripodal porphyrin receptors reported by the groups of Pascu and Sanders [25]. At first sight, their receptors do not strictly fit in the category of molecular tweezers, since they feature three recognizing motifs each, but as we shall see their binding mode is that of a tweezer.…”
Section: Porphyrin-based Molecular Tweezers For Fullerenesmentioning
confidence: 97%
“…We will conclude this section dedicated to porphyrin tweezers for fullerenes with the work on tripodal porphyrin receptors reported by the groups of Pascu and Sanders [25]. At first sight, their receptors do not strictly fit in the category of molecular tweezers, since they feature three recognizing motifs each, but as we shall see their binding mode is that of a tweezer.…”
Section: Porphyrin-based Molecular Tweezers For Fullerenesmentioning
confidence: 97%
“…29 Various tripod systems have been synthesized with the goal of fullerene complexation ( Figure 9). 30 One such scaffold involves a tripod with rigid linkers; this system is proposed to make a supramolecular network wherein the net stoichiometry is expected to be 1 : 2 (tripod to fullerene). On the basis of an experimental analysis, it was concluded that each fullerene is always held by two porphyrins.…”
Section: Fullerenesmentioning
confidence: 99%
“…In a recent example, Sanders and coworkers described the synthesis and fullerene complexation of two different tripodal porphyrin hosts (26-27) by means of X-ray crystallography, and NMR and fluorescence titrations [31]. Surprisingly, the binding of C 60 resulted to be completely different in solution and in the solid state.…”
Section: Receptors For Fullerenes Based On Planar Recognizing Units 73mentioning
confidence: 99%